2013
DOI: 10.1111/jpm.12029
|View full text |Cite
|
Sign up to set email alerts
|

Towards new ways of working in dementia: perceptions of specialist dementia care nurses about their own level of knowledge, competence and unmet educational needs

Abstract: It is expedient to consider new ways in which dementia care services may be configured to meet increasing demographic, societal and regulatory demands. Greater equity in the distribution of clinical responsibility across multidisciplinary teams has been suggested as one method that may offer a range of benefits to both the service user and the service itself. However, within the dementia workforce there are concerns about inconsistency and variability in both knowledge of dementia and competency in meeting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 8 publications
5
23
0
1
Order By: Relevance
“…Consistent with prior research, the authors of the current article found that staff members wanted to obtain a better understanding of how to actively involve patients with dementia in their own care and adopt new skills for managing behaviors (Kolanowski et al, 2010;Page & Hope, 2013). Staff appeared to have insight that they needed more handson skills training.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Consistent with prior research, the authors of the current article found that staff members wanted to obtain a better understanding of how to actively involve patients with dementia in their own care and adopt new skills for managing behaviors (Kolanowski et al, 2010;Page & Hope, 2013). Staff appeared to have insight that they needed more handson skills training.…”
Section: Discussionsupporting
confidence: 62%
“…The third highest identified need (i.e., coping with challenges) is also supported by previous research (Edberg et al, 2008;Kolanowski et al, 2010). The emotional and physical stresses of caring for individuals with behavioral challenges is well documented in the formal caregiving literature (Brodaty et al, 2003;Schmidt, Dichter, Palm, & Hasselhorn, 2012;Zwijsen et al, 2014).Consistent with prior research, the authors of the current article found that staff members wanted to obtain a better understanding of how to actively involve patients with dementia in their own care and adopt new skills for managing behaviors (Kolanowski et al, 2010;Page & Hope, 2013). Staff appeared to have insight that they needed more handson skills training.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Huizenga et al (2016) reflected similar concerns with a Registered Nurses Specialized in Gerontology and The need to start by articulating such a curriculum in the UK reflects stagnation of the speciality over recent years. In England, due to limited opportunities, a large proportion of nurses working in older person's services do so without a recognised post-registration qualification in gerontologic nursing; this is in stark contrast to other specialities such as intensive care (Page and Hope, 2013). In addition, there is concern that older person's specific content in undergraduate curricula is inadequate and fails to reflect the complexity of this population (Deschodt et al, 2009).…”
Section: Accepted M Manuscriptmentioning
confidence: 97%
“…Dylematy etyczne w opiece geriatrycznej często pojawiają się także na skutek konfliktu między zobowiązaniami wypływającymi z roli zawodowej profesjonalisty i związanymi z nią obowiązkami prawnymi i etycznymi a autonomią i prawem do samostanowienia pacjenta [5][6][7]. Ponadto problemy etyczne wynikające z opieki nad populacją geriatryczną związane są z brakiem dostatecznej znajomości istoty procesu starzenia i towarzyszach mu zaburzeń (zwłaszcza otępiennych), a także uwarunkowaniami systemowymi (ograniczeniami w dostępie do świad-czonej opieki adekwatnej do potrzeb) [8] i postawami społecznymi (ageizm) [9,10].…”
Section: Wstępunclassified